2014
DOI: 10.1093/cercor/bhu274
|View full text |Cite
|
Sign up to set email alerts
|

Causal Influence of Articulatory Motor Cortex on Comprehending Single Spoken Words: TMS Evidence: Figure 1.

Abstract: Classic wisdom had been that motor and premotor cortex contribute to motor execution but not to higher cognition and language comprehension. In contrast, mounting evidence from neuroimaging, patient research, and transcranial magnetic stimulation (TMS) suggest sensorimotor interaction and, specifically, that the articulatory motor cortex is important for classifying meaningless speech sounds into phonemic categories. However, whether these findings speak to the comprehension issue is unclear, because language … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
52
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 73 publications
3
52
0
Order By: Relevance
“…They found that in the absence of a task, TMS to motor cortex resulted in nonspecific modulations of auditory cortex; articulator-specific effects of TMS were only seen during a working memory task. This line of research suggests that the above TMS studies, which did not have control tasks, can be explained by their use of phonological categorization (but see Schomers et al, 2014, for their interpretation of the KriegerRedwood study). It is currently unclear how fMRI-adaptation approaches, which have shown greater effects of phonemic category (e.g., Chevillet et al, 2013), can be reconciled with MVPA approaches such as ours, which show little or no sensitivity to phonological categories in motor cortex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that in the absence of a task, TMS to motor cortex resulted in nonspecific modulations of auditory cortex; articulator-specific effects of TMS were only seen during a working memory task. This line of research suggests that the above TMS studies, which did not have control tasks, can be explained by their use of phonological categorization (but see Schomers et al, 2014, for their interpretation of the KriegerRedwood study). It is currently unclear how fMRI-adaptation approaches, which have shown greater effects of phonemic category (e.g., Chevillet et al, 2013), can be reconciled with MVPA approaches such as ours, which show little or no sensitivity to phonological categories in motor cortex.…”
Section: Discussionmentioning
confidence: 99%
“…D'Ausilio and colleagues (2009) administered TMS to lip-and tonguerelevant motor areas during the discrimination of lip-and tongue-articulated speech sounds and found a double Schomers, Kirilina, Weigand, Bajbouj, and Pulvermüller (2014) delivered facilitory TMS to lip and tongue areas of the motor cortex during a word-to-picture matching task in order to measure comprehension effects. It was found that words with an alveolar PoA were matched faster following TMS to the tongue area of the motor cortex than to the lip area, although the reverse was not found for labial PoA, and no differences in accuracy were observed.…”
Section: Discussionmentioning
confidence: 99%
“…Such a predictive coding scheme for speech perception could be achieved if speech-related activity in auditory areas leads to activation of articulatory motor regions for the purposes of internal, motoric simulation, in a process automatized by Hebbian correlation learning (Braitenberg and Pulvermüller, 1992). For example, auditory-motor co-activation may be effected by the oscillatory activity of neuronal circuits distributed across inferior-frontal and superior-temporal areas, which reach into articulatory motor cortex (Schomers et al, 2014). Perceiving speech then triggers the automatic resonance of these circuits;…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, overt movement or stimulation of these motor areas has a causal effect on simultaneous processing of specific types of action words. Vice versa, action word processing may impact on specific motor mechanisms, with effects visible in behaviour and in electrophysiological brain recordings 2 Fischer & Zwaan, 2008;Glenberg & Kaschak, 2003;Ibanez et al, 2012;Pulvermü ller, Hauk, Nikulin, & Ilmoniemi, 2005;Rueschemeyer, Lindemann, van Elk, & Bekkering, 2009;Schomers & Pulvermü ller, 2016;Schomers, Kirilina, Weigand, Bajbouj, & Pulvermü ller, 2015;Shebani & Pulvermü ller, 2013). Fifth, and finally, movement disorders and clinical impairments to motor systems are associated with specific processing impairments or abnormalities for action-related words which call on action knowledge in the retrieval of their meaning (Bak & Chandran, 2012;Boulenger et al, 2008;Cardona et al, 2014;Cotelli et al, 2006;García & Ibañez, 2014;Grossman et al, 2008;Kemmerer, 2015;Neininger & Pulvermü ller, 2001Pulvermü ller et al, 2010).…”
mentioning
confidence: 99%